A robust algorithm to solve the signal setting problem considering different traffic assignment approaches - Adacher, Ludovica; Gemma, Andrea (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we extend a stochastic discrete optimization algorithm so as to tackle the signal setting problem. Signalized junctions represent critical points of an urban transportation network, and the efficiency of their traffic signal setting influences the overall network performance. Since road congestion usually takes place at or close to junction areas, an improvement in signal settings contributes to improving travel times, drivers` comfort, fuel consumption efficiency, pollution and safety. In a traffic network, the signal control strategy affects the travel time on the roads and influences drivers` route choice behavior.
Keywords: genetic algorithms; surrogate method; traffic signal synchronization; traffic assignment; simulation